2 Improving the timeliness of care for children with testicular torsion in the pediatric emergency department. (25th November 2019) - Chinta, Sri; Gray, Matthew; Kopetsky, Matthew; Baumer-Mouradian, Shannon; Drendel, Amy; Roth, Elizabeth; Ferguson, Catherine; Boyd, Kevin; Brousseau, David
Abstract : Background: Early diagnosis and timely surgery are critical to treat children with testicular torsion. Only 33% of patients met the hospital goal of 'critical diagnosis to operating room time of 60 minutes or less [CDOR60]' prior to starting the QI project. Objectives: The objective of the quality improvement project was to increase the utilization of TWIST score, a validated clinical scoring system from 0% to 80% over 12 months period for children evaluated for testicular torsion, as a means of increasing the number of patients with CDOR60. Methods: Deploying the Institute for Healthcare Improvement Model for Improvement, we formulated an aim statement and identified key drivers. Of our interventions, successful implementation of the TWIST score in the emergency department (ED), with a guideline to support earlier notification of urology for high risk patients with testicular pain, was determined to be the highest impact intervention. We educated providers and gave biweekly feedback about guideline adherence, created order panels and documentation tabs in our electronic medical record to encourage documentation. Results: Between September 2018 and April 2019, TWIST score documentation improved to >80% and was sustained at that rate for 4 months. After implementation of the guideline, the critical diagnosis to OR time of 60 minutes or less was achieved in 12 out of 16 patients diagnosed with testicular torsion in the ED [75%] compared to our baseline of 33%. Conclusions: A quality improvement project to improve the timeliness of care for children with testicular torsion resulted in delivery of expedited surgical care for these patients.